KETAHANAN DAN KEMANDIRIAN PANGAN RUMAH TANGGA TANI DAERAH MARGINAL DI KABUPATEN BOJONEGORO - Jangkung Handoyo Mulyo; Sugiyarto Sugiyarto; Arif Wahyu Widada (Agro Ekonomi, 2015)
Food security and food self-sufficiency at household level are much determined by their farm production. Meanwhile, some areas considered as the marginal area are constrained by limited support of natural resources. Thus, many households lived in marginal area will face food insecurity. This study aimed to understand the households’ food security level, both measured by using the Energy Sufficiency Score (AKE) and the Food Expenditure Share (PPP). Furthermore, this study also tries to identify the food self-sufficiency level among rural marginal household in Bojonegoro Regency. The result of study shows that there is a wide disparity among rural household in the food/energy intake, this is shown by the average level of food/energy intake level that is considered high (87%), meanwhile there is 53% of the households categorized as the food insecure household. Based on the Food Expenditure Share level, most of the households are categorized as food secure households. The food self-sufficiency, particularly rice, have been attained.